PENGARUH ORGANIZATION COMMITMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN PERSON-ORGANIZATION FIT SEBAGAI MODERATOR PADA KARYAWAN OAKWOOD HOTEL & RESIDENCES SURABAYA - Ecinsia, Emi; Nugroho, J.L. Eko; Widjaja, M.E. Lanny Kusuma (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study aims to determine the effect of organizational commitment on organizational citizenship behavior with person-organization fit as a moderator for Oakwood Hotel & Residences Surabaya employees. This research will see the extent to which the role of perceived organizational support, employee development, and organization commitment in influencing organizational citizenship behavior of Oakwood Hotel & Residences Surabaya employees. This research uses a quantitative approach using Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis using SmartPLS software with a sample size of 115 respondents. This study shows the results that perceived organizational support, employee development, and organization commitment have a positive and significant effect on organizational citizenship behavior and person-organization fit moderate the relationship between organization commitment and organizational citizenship behavior.